SCIENTIFIC THEORETICAL ANALYSIS OF THE CATEGORY OF NORMAL CREATIVITY (The Role of Exact Sciences in the Era of Modern Development, 2024)
In this thesis, the category of norm creation, which is one of the main types of law creation, is analyzed from a scientific and theoretical point of view. Also, in this thesis, scientific and practical suggestions are given regarding the basic concepts of norm creativity.